PIN SITE CARE USING CHLORHEXIDINE; CASE STUDY REPORT - Desak Wayan Suarsedewi (Prodi Kesehatan Masyarakat FKM UIN Sumatera Utara Medan, 2017)
ABSTRACT   Pin site infections were a common complication of external fixation that places a significant burden on the patient and healthcare system. Such infections increase the number of clinic visits required during a patient's course of treatment, can result in the need for additional treatment including antibiotics and surgery, and most importantly can compromise patient outcomes should osteomyelitis or instability result from pin loosening or need for pin or complete construct removal. Factors that may influence the development of pin site infections include patient-specific risk factors, surgical technique, pin design characteristics, use of prophylactic antibiotics, and the post-operative pin care protocol including cleansing, dressing changes, and showering. Despite numerous studies that work to derive evidence-based recommendations for prevention of pin site infections, substantial controversy exists in regard to the optimal protocol. This review comprehensively evaluated the current literature to provide an overview of factors that may influence the incidence of pin site infections in patients undergoing treatment with external fixators, and concludes with a description of the preferred surgical and post-operative pin site protocols employed by the senior authors (ATF and SRR).   Keywords: External fixation, Pin site, Pin tract/track, Infection, Prevention, Chlorexidine solution